Implementasi Pathfinding pada Game Edukasi Pengenalan Huruf Alphabet Menggunakan Algoritma A Star - Septa (JoMMiT, 2026)
Educational games for alphabet recognition have become an effective and engaging learning tool for early childhood. One technique to enhance the learning experience in these games is the implementation of the A* (A Star) algorithm in the pathfinding process. This study involves the implementation of the A* algorithm to guide the movement of enemies towards players on a map consisting of alphabet letters, obstacles, and players. Simulation results demonstrate that the A* algorithm efficiently determines the shortest path, creating customizable difficulty levels within the game. Additionally, the integration of interactive features, letter pronunciation sound, and captivating animations enhances the appeal of the learning experience. Personalized difficulty levels and diversified content ensure inclusivity in the learning experience. Through further refinement and development, this game has the potential to be a valuable learning resource, supporting the development of alphabet skills in early childhood.